Technology Entrepreneurship Project (ENT 600) : Reebok / Iskandar Zulkarnain Dali - Dali, Iskandar Zulkarnain (2021)
This case project is to get a chance to doing a research about the manufacture a product that I am interest which is Cap from Reebok Brands, sport retailer. So as a student in UiTM Perlis, this project is part of my study. Firstly, the first research from this project is about the general information regarding to the primary and secondary sources who act as a references to collect the data. So, based on this study, the objective is to figure the background, organizational structure, product, service, SWOT analysis either show the strength, weakness, opportunity and treat of the product that I am research for from Reebok Brand. Based on the SWOT analysis, I figure that are many problems that come out regarding to this product. So, here the main problems that this product faces which is design and the colour of product is not suitable and have low interest to attract customer to buy it. Lastly, regarding to this study case, I will provide the best solution based on the main problem that this company face.